Pengukuran Kinerja Keuangan dengan Pendekatan Economic Value Added (EVA) dan Market Value Added (MVA) Sebelum dan Setelah Merger pada Perusahaan Go Public yang Tercatat di Bursa Efek Indonesia (BEI) Periode 2010-2012 - Soewito SOEWITO; Aprisa Kusumawati (SOSIALITA, 2017)
The aims of this study was to knowing Company Performance Measurement through determine and analyze the differences in financial performance before and after the merger with Economic Value Added (EVA) and Market Value Added (MVA) aprroach to the company which went public listed on the Stock Exchange and the merger. This research is a comparative with quantitative methods. The sample in this research using purposive sampling method amounted to 6 companies of the population of 82 companies, with data collection in the form of documentation in the form of the announcement of the merger, the share price and annual financial statements. The results of this study indicate that there are significant differences between the financial performance using the Economic Value Added (EVA) method before and after the merger, and there are significant differences between the financial performance using the Market Value Added (MVA) before and after the merger.